Reduced eye optical quality contributes to worse chromatic thresholds in aging - Costa, Marcelo Fernandes; Rego, Livia Soledade; Henriques, Leonardo Dutra; Martins Gaddi, Carlo; Souza, Givago Silva (Frontiers in Integrative Neuroscience, 2023)
Purpose: Aging causes substantial changes in the intraocular lens, which leads to a reduction in chromatic perception. We aimed to analyze the ocular light dispersion component in relation to the damage in color vision by aging. Methods: We used the C-Quant to psychophysically quantify the intraocular straylight and compare ocular dispersion degrees with the chromaticity thresholds measured by Trivector protocol of the Cambridge Colour Test. We tested 76 subjects aged from 24 to 68 (35 males) with normal visual acuity and no clinical evidence of cataract. Results: The results show that there is a positive correlation between the ocular dispersion of light and the chromaticity thresholds for the protan (r= . 24; p=.040), deutan (r= .36; p=.002) and tritan (r= .26; p=.035) color confusion axes. The other 2 quality measurement parameters estimated in C-Quant were not correlated with chromaticity thresholds, suggesting any problems with the quality of the measurement performed. Conclusions: Our results show that the increase in ocular light dispersion that occurs with aging negatively impacts the chromaticity threshold similarly on the three color confusion axes.